2018
DOI: 10.1002/eji.201847663
|View full text |Cite
|
Sign up to set email alerts
|

Airway epithelial TSLP production of TLR2 drives type 2 immunity in allergic airway inflammation

Abstract: Epithelial cells (ECs)‐derived cytokines are induced by different stimuli through pattern recognition receptors (PRRs) to mount a type‐2‐cell‐mediated immune response; however, the underlying mechanisms are poorly characterized. Here, we demonstrated asthmatic features in both primary bronchial epithelial cells (pBECs) and mouse model using several allergens including ovalbumin (OVA), house dust mite (HDM), or Alternaria alternata. We found that toll‐like receptor 2 (TLR2) was highly induced in ECs but not den… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
27
0
9

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(38 citation statements)
references
References 48 publications
2
27
0
9
Order By: Relevance
“…The present study used OVA model, which has been the most widely used pre-clinical allergic asthma model and recapitulates many of the hallmarks of allergic asthma in humans, however, bio-models offer other allergen-induced allergic model, such as house dust mite (HDM), Alternaria, papain and IL-33, with each mimicking the major features of human asthma. When OVA, HDM, or Alternaria was given via inhalation or intranasally, each of them can be recognized and sensed by TLRs reportedly, especially TLR2 (40). Similarly, intranasally given IL-33 is reported can induce direct stimulation of TLR2 on ILC2s (39).…”
Section: Discussionmentioning
confidence: 97%
“…The present study used OVA model, which has been the most widely used pre-clinical allergic asthma model and recapitulates many of the hallmarks of allergic asthma in humans, however, bio-models offer other allergen-induced allergic model, such as house dust mite (HDM), Alternaria, papain and IL-33, with each mimicking the major features of human asthma. When OVA, HDM, or Alternaria was given via inhalation or intranasally, each of them can be recognized and sensed by TLRs reportedly, especially TLR2 (40). Similarly, intranasally given IL-33 is reported can induce direct stimulation of TLR2 on ILC2s (39).…”
Section: Discussionmentioning
confidence: 97%
“…In addition, TSLP derived from epithelial cells also plays an important role in the initiation of allergic inflammatory induction 31,32 . Epithelial cells were activated by external stimulus (such as allergens, microorganisms, air pollutants, etc.)…”
Section: Discussionmentioning
confidence: 99%
“…Another study using the HDM model demonstrated that IL‐37 could suppress the induced concentrations of Th2 and asthma‐related cytokines IL‐4, IL‐6 and IL‐13 in lung homogenate of humanized acute allergic asthmatic mice . TSLP affects the development of Th2 immune responses at multiple stages through its effects on DCs and CD4 + T cells . We previously demonstrated that the neutralization of TSLP with an anti‐TSLP monoclonal antibody inhibited HDM‐induced Th2 responses .…”
Section: Discussionmentioning
confidence: 99%